Nutritive value of wild edible and cultured mushrooms - Akyuz, Mehmet; Kirbag, Sevda (Tubitak Scientific & Technological Research Council Turkey, 2010)
The nutritive value of Pleurotus ostreatus (Jacq. ex Fr.) Kumm., Pleurotus sajor-caju (Fr.) Singer, and Agaricus bisporus (Large) Sign. was determined. Dry matter, moisture, crude ash, protein, fat, cellulose, organic matter, and nitrogen-free extract were 89.7%-90.3%, 9.7%-10.3%, 6.0%-13.7%, 27.8%-41.6%, 0.5%-1.3%, 10.0%-16.2%, 76.0%-84.0%, and 26.7%-36.8% of dry weight, respectively. Mineral element contents were 14.1-45.6 g K kg(-1), 0.2-1.2 g Ca kg(-1), 0.4-1.9 g Mg kg(-1), and 0.2-0.9 g Na kg(-1) as macronutrients, and 176.5-838.0 mg Fe kg(-1), 35.0-46.0 mg Zn kg(-1), 4.8-65.4 mg Mn kg(-1), 6.5-21.5 mg Cu kg(-1), 0.0-11.5 mg Cr kg(-1), and 0.0-1.65 mg Cd kg(-1) micronutrients (dry wt). Furthermore, toxic elements, such as Pb, Ni, and Co, were not detected in any of the 3 species of mushroom.
Yenen yabani ve kültür mantarlarin besin de?erleri
Keywords: Pleurotus spp.; A. bisporus; nutritive value; mineral element